Scientific Education among Muslims in Northern Nigeria: The Influence of Middle Eastern and Mediterranean Scholarship - Mukhtar Umar Bunza; Lawal Abdulkarim (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
In the study of Islamic education, the scientific and medical contributions of Muslims globally are incongruously positioned. In most cases, Islamic education is completely divorced from its conventional scientific research and experimentation known and appreciated in its early and classical periods. Science and medicine are not alien in Islamic epistemology, though, have suffered gross neglect in the Muslim World in recent centuries. However, the universality and connectivity among the Muslims in the world since the beginning of the Islamic mission has been one of the gluing and cementing factors in the Muslim world intellectually and culturally, which made spread and diffusion of literature and scholarship across Muslim communities reciprocally. It is thus, not a surprise to find that, not only on the spiritual and educational facets but also in scientific and medical spheres the classical writers of the Middle Eastern and Mediterranean regions got their ways and significantly impacted the Muslim scholars of the nineteenth century northern Nigeria. The paper, therefore, aims at tracing and analyzing the extent of influence of those (Middle Eastern and Mediterranean regions) scientific literatures on the perception, motivation, as well as research, documentation, and experimentation in fields of sciences and medicine in Muslim Northern Nigeria. Special consideration will be given to the works by Sultan Muhammad Bello, d. 1837, who wrote quite a number of treatises on different aspects of sciences, followed by Sheikh Abdullahi Fodiyo d. 1829, and others who followed after them. The research will also explore how in turn, their educational works on scientific and medical research also impacted on the Muslim societies in Nigeria and beyond, especially in the codification and enlistment of the scientific resource materials on the wider educational spheres and the curricular of the Muslim societies of the area, since the last two centuries.